Narrating well-being in the context of precarious prosperity: An account of agency framed by culturally embedded happiness and gender beliefs - Sieber, Rebekka (My University, 2015)
This article sets out to critically examine the accounts of well-being produced by a middle-aged Swiss woman living in precarious prosperity. By taking on a feminist reading of the narrative on well-being, the article challenges the taken for granted assumption of the powerful agent in thriving societies. Insights from literature on happiness in nations and gender beliefs enabled addressing the woman’s capability to exert agency, while acknowledging the influence of the context in which narratives are embedded. In addition, the presence of a non-national interviewer appears to be an incentive for the interviewee’s compliance with cultural meta-narratives. The approach of well-being as ‘agential flourishing’ proved helpful in assessing the woman’s capability on a gendered career path in atypical employment to deal with precariousness.
Keywords: Agency; culturally embedded happiness; gender; precarious prosperity; well-being